Three Solutions for Inequalities Dirichlet Problem Driven by p(x)-Laplacian-Like - Zhou Qing-Mei; Ge Bin (Abstract and Applied Analysis)
A class of nonlinear elliptic problems driven by p(x)-Laplacian-like with a nonsmooth locally Lipschitz potential was considered. Applying the version of a nonsmooth three-critical-point theorem, existence of three solutions of the problem is proved.